Photo-Biocatalytic Cascades for the Synthesis of Volatile Sulfur Compounds and Chemical Building Blocks - Lauder, Kate; Castagnolo, Daniele (Synlett, 2020)
Biocatalysis is a branch of catalysis that exploits enzymes to perform highly stereoselective chemical transformations under mild and sustainable conditions. This Synpact highlights how biocatalysis can be used in the synthesis of chiral 1,3-mercaptoalkanols, an important class of compounds responsible for the flavours and aromas of many foods and beverages. The identification of two ketoreductase (KRED) enzymes able to reduce prochiral ketone precursors enantioselectively to 1,3-mercaptoalkanols bearing a C–O stereocentre is presented. In addition, the combination of a photocatalytic thia-Michael reaction to access prochiral ketones with subsequent KRED-biocatalysed reduction in a one-pot cascade is presented. Photo-biocatalysed cascades represent one of the new and most intriguing challenges in synthetic chemistry, because the combination of different catalytic methodologies in domino processes offers unique opportunities to outperform sequential reactions with a high degree of selectivity and the avoidance of the need to isolate reaction intermediates.1 Introduction2 Biocatalytic Synthesis of 1,3-Mercaptoalkanols3 Photo-Biocatalytic Synthesis of 1,3-Mercaptoalkanols4 Photo-Biocatalysed Cascade Reactions5 Conclusions
Keywords: biocatalysis; ketoreductase; photobiocatalytic cascade; photocatalysis; mercaptoalkanols